2004
DOI: 10.2903/j.efsa.2004.73
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of the Scientific Panel on contaminants in the food chain [CONTAM] related to Deoxynivalenol (DON) as undesirable substance in animal feed

Abstract: "the TDI of 1 mg/kg b.w./day" has been replaced by "the TDI of 1 µg/kg b.w./day". At low doses decreased feed intake seems to be attributable to the stimulation of the synthesis of pro-inflammatory cytokines under practical conditions, whilst at higher concentrations vomiting is triggered by the interaction of DON with serotonergic and dopaminergic receptors. Pigs have been identified as the most sensitive animals species regarding these adverse effects. However, at present the available data on exposure via f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 114 publications
0
9
1
Order By: Relevance
“…Cereal straw, which is commonly used as bedding material and which may be chewed and eaten, is a potential source of these mycotoxins, too (Gutzwiller 2006). DON and ZEA affect feed intake, growth performance and fertility of pigs, which are the most sensitive farm animal species to these two mycotoxins (EFSA 2004(EFSA , 2011. The diagnosis of DON and ZEA intoxication in pigs is usually based on the analysis of feed and straw.…”
Section: Introductionmentioning
confidence: 99%
“…Cereal straw, which is commonly used as bedding material and which may be chewed and eaten, is a potential source of these mycotoxins, too (Gutzwiller 2006). DON and ZEA affect feed intake, growth performance and fertility of pigs, which are the most sensitive farm animal species to these two mycotoxins (EFSA 2004(EFSA , 2011. The diagnosis of DON and ZEA intoxication in pigs is usually based on the analysis of feed and straw.…”
Section: Introductionmentioning
confidence: 99%
“…Both an intact C12-13 epoxide and a double bond at C9-10 position are essential for this inhibitory activity. DON binds to the 60 S subunit of the eukaryotic ribosome and interferes with the action of peptidyl transferase [25,26]. In one study using human intestinal epithelial Caco-2 cells (derived from colorectal carcinoma tissue), it was found that there was a concentration-dependent effect of DON on total cellular protein synthesis and content [27].…”
Section: Deoxynivalenolmentioning
confidence: 99%
“…Most, but not all, of these mycotoxins are produced by the Fusarium species. Although these mycotoxins are significant contaminants when entering the food chain directly via food of plant origin, they are not considered relevant in food of animal origin because their carry-over from feed to animal-derived food products is negligible [9][10][11][12]. However, Fusarium species are also responsible for the production of minor mycotoxins, namely, enniatins and beauvericin, which are currently in the center of interest because of the wide range of their biological activities, as described in details bellow.…”
Section: Introductionmentioning
confidence: 99%